Penentuan Dosis Efektif Organ at Risk terhadap Penyinaran Kepala dengan Pesawat CT-Scan Merek Siemens 128 Slice di RSUP Sanglah Denpasar - Shatriani Wulandary Sipul; Ida Bagus Made Suryatika; I Wayan Balik Sudarsana (Universitas Hamzanwadi, 2022)
Research has been carried out on determining the effective dose of organ at risk for head irradiation using a Siemens 128 slice CT-Scan at Sanglah Hospital, Denpasar. The data used in this study are secondary data from medical records or CT-Scan archives irradiating the head, namely CTDIVOL and DLP data for male and female patients aged 26-45 years. This study aims to determine the amount of DE and Deff received by male and female patients and to determine the feasibility of using CT-Scan in the installation. The DE value for the head section is obtained by multiplying the DLP value by the conversion factor (k). The DE analysis in the head was carried out using the standard value of the Regulation of the Head of Bapeten No. Rek: LT/STI/KN 01/P2STPFRZR1/077/2016, while Deff is obtained from the CTDIVOL value multiplied by Wt. The results of the calculation of Deff received by male patients were 0.51 ± 0.01 mGy and female patients were 0.48 ± 0.01 mGy. The results of the DE calculation for male patients were 2.38 ± 0.08 mGy and female patients were 2.28 ± 0.08 mGy. The result of the head DE calculation according to BAPETEN guidelines is 2.94 mGy. Based on the results of the DE calculation on the head, the DE value is still within the normal limits issued by the BAPETEN guidelines so that the Siemens 128 Slice CT-Scan in the installation is still suitable for use for CT-Scan examination of the head.